The Fanconi syndrome of cystinosis: insights into the pathophysiology - Sakarcan, Abdullah (The Turkish Journal of Pediatrics, 2002)
Cystinosis is a lysosomal storage disease, and is one of the most common causes of the Fanconi syndrome. In vitro studies of the cystine-loaded tubule provided insights into the pathophysiology of the proximal tubular defect. Proximal tubules loaded with cystine have a generalized proximal tubule transport defect characteristic of the Fanconi syndrome. The decrease in proximal tubular transport with cystine loading is due to a decrease in active transport. In cystine-loaded tubules the ATP production is severely compromised. The cystine-loaded tubule has a lower intracellular phosphate concentration than that of control tubules. This low intracellular phosphate concentration in cystine-loaded tubules likely plays an important role in maintaining intracellular ATP level. Preservation of intracellular phosphate at control levels prevents the decrease in intracellular ATP and the proximal tubule respiratory dysfunction with cystine loading.